Advances in virus research. Volume 92 - Maramorosch, Karl; Murphy, Frederick A.; ScienceDirect eBooks (Waltham, MA : Academic Press, 2015)
Published since 1953, Advances in Virus Research covers a diverse range of in-depth reviews, providing a valuable overview of the current field of virology.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed February 25, 2015).
Elsevier
Keywords: Virologie; Virologie -- Recherche; Virus Epstein-Barr.; Biologie moléculaire.; Virus -- Reproduction; Virology; Virology -- Research; Virology; Virology -- Research; Electronic books